Birefringence induced Vernier effect in optical fiber modal interferometers for enhanced sensing - Li, Kaiwei (2019)
We report a simple and effective method to improve the sensitivities of fiber-optic modal interferometers with birefringence induced Vernier effect. Taking optical microfiber coupler as an example, we study the sensitivity enhancement of a microfiber coupler for refractive index (RI) sensing both theoretically and experimentally in the RI range of 1.33–1.35 where bioassays are typically carried out. Numerical results show that by tracing the wavelength shifts of dips in the envelope formed by the Vernier effect, RI sensitivities can be improved by almost one order of magnitude compared to the sensors without the Vernier effect. Then we experimentally achieve an ultra-high sensitivity of 35,823.3 nm/RIU using a microfiber coupler with a width of 3.2 μm. More importantly, we apply this ultra-sensitive sensor to detect human cardiac troponin, and a limit of detection of 1 ng/mL is achieved. This sensor is simple in configuration andcan serve as a bio-photonic platform for clinical diagnostics environmental monitoring and food safety.